Yeast - Huxley, Thomas Henry, 1825-1895 (Salt Lake City, UT : Project Gutenberg, 2001)
"Yeast" by Thomas Henry Huxley is a scientific publication written in the late 19th century. This work explores the fascinating processes involved in the phenomenon of fermentation, focusing particularly on yeast, a ubiquitous organism that plays a crucial role in the transformation of sugars into alcohol and carbon dioxide. Huxley aims to demystify the science behind fermentation, linking it to broader biological and chemical principles. In this lecture, Huxley begins with a discussion of common observations related to yeast, followed by a detailed investigation of its nature and properties. He explains how the yeast organism, referred to as "Torula," is a type of fungus that actively consumes sugar and produces alcohol and carbon dioxide through vital processes. The author highlights various experiments that establish the relationship between yeast and fermentation, including studies on the gases produced and the organic compounds formed. Huxley concludes with an exploration of the implications of yeast studies for understanding disease transmission, drawing parallels between infectious agents and the spores of yeast, which can propagate fermentation like contagion. Through his analysis, Huxley emphasizes the interconnectedness of life and fundamental biological processes. (This is an automatically generated summary.)
Release date is 2001-11-01
Produced by Amy E. Zelmer, and David Widger
Keywords: Yeast